2009
DOI: 10.1002/smll.200800003
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size, Surface Coating, and PEGylation Influence the Biodistribution of Quantum Dots in Living Mice

Abstract: This study evaluates the influence of particle size, PEGylation, and surface coating on the quantitative biodistribution of near-infrared-emitting quantum dots (QDs) in mice. Polymer- or peptide-coated 64Cu-labeled QDs 2 or 12 nm in diameter, with or without polyethylene glycol (PEG) of molecular weight 2000, are studied by serial micropositron emission tomography imaging and region-of-interest analysis, as well as transmission electron microscopy and inductively coupled plasma mass spectrometry. PEGylation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
327
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(342 citation statements)
references
References 32 publications
4
327
2
2
Order By: Relevance
“…The glomerular filtration apparatus, taken in its entirety, possesses an effective size cutoff of 10 nm, and it is responsible for the rapid renal clearance of small nanoparticles. Many nanoparticle-based contrasting agents for in vivo imaging were designed to be smaller than this size cutoff (11,12). Prolonged residency of nanoparticles in the kidney has been shown to induce toxicity in the form of cell shrinkage because of excessive nanoparticle uptake by renal cells (13,14).…”
mentioning
confidence: 99%
“…The glomerular filtration apparatus, taken in its entirety, possesses an effective size cutoff of 10 nm, and it is responsible for the rapid renal clearance of small nanoparticles. Many nanoparticle-based contrasting agents for in vivo imaging were designed to be smaller than this size cutoff (11,12). Prolonged residency of nanoparticles in the kidney has been shown to induce toxicity in the form of cell shrinkage because of excessive nanoparticle uptake by renal cells (13,14).…”
mentioning
confidence: 99%
“…Lifetime maps were calculated by determining the lifetime from the fluorescence decays of all the photon counts registered for each pixel. Scale bar 10 μm (Linkov et al 2008;Schipper et al 2009). Recently, Zheng et al (2011) studied renal clearance of glutathione-coated luminescent AuNCs and revealed that only 3.7 % of the clusters accumulated in the liver; over 50 % of the clusters were found in urine within 24 h after intravenous injection, which is comparable to the quantum dots with the best renal clearance efficiency (Soo Choi et al 2007).…”
Section: Fluorescence Imaging Of Gold Nanoclusters In Vivomentioning
confidence: 99%
“…A few other reports have focused on radiolabeling QDs with PET isotopes such as 18 F (t1/2: 110 min) and 64 Cu. [48][49][50] However, neither incorporation of a targeting moiety nor optical imaging was carried out in these studies. Due to the difficulties in quantifying the fluorescence signal in vivo and many other technical challenges which remain to be solved, in vivo imaging of QDs is so far mostly qualitative or semiquantitative.…”
Section: Molecular Imaging With Radiolabeled Nanoparticlesmentioning
confidence: 99%